Kinetics, thermodynamics, and catalysis of the cation incorporation into GeO2, SnO2, and (SnxGe1−x)O2 during suboxide molecular beam epitaxy - Wenshan Chen; Kingsley Egbo; Joe Kler; Andreas Falkenstein; Jonas Lähnemann; Oliver Bierwagen (APL Materials)
Rutile GeO2 is a promising ultra-wide bandgap semiconductor for future power electronic devices whose alloy with the wide bandgap semiconductor rutile-SnO2 enables bandgap engineering and the formation of heterostructure devices. The (SnxGe1−x)O2 alloy system is in its infancy, and molecular beam epitaxy (MBE) is a well-suited technique for its thin-film growth, yet it presents challenges in controlling the alloy composition and growth rate. To understand and mitigate this challenge, the present study comprehensively investigates the kinetics and thermodynamics of suboxide incorporation into GeO2, SnO2, and (SnxGe1−x)O2 during suboxide MBE (S-MBE), the latest development in oxide MBE using suboxide sources. We find S-MBE to simplify the growth kinetics, offering better control over growth rates than conventional MBE but without supporting cation-driven oxide layer etching. During binary growth, SnO incorporation is kinetically favored due to its higher oxidation efficiency and lower vapor pressure (limiting its loss by desorption) compared to those of GeO. In (SnxGe1−x)O2 growth, however, the GeO incorporation is preferred and the SnO incorporation is suppressed, indicating a catalytic effect, where SnO promotes GeO incorporation. The origin of this catalytic effect cannot be understood by comparing the binary kinetics or thermodynamics (cation–oxygen bond strengths), thus calling for further theoretical studies. Our experimental study provides guidance for controlling the growth rate and alloy composition of (SnxGe1−x)O2 in S-MBE, highlighting the impact of the substrate temperature and active oxygen flux besides that of the mere SnO:GeO flux stoichiometry. The results are likely transferable to further physical and chemical vapor deposition methods, such as conventional and hybrid MBE, pulsed laser deposition, mist-, or metalorganic chemical vapor deposition.